Three-dimensional spatial reconstruction of the gunshot injuries in the practice of forensic medicine - Bachynskyy, V. T.; Zmiyevska, Y. H.; Savka, I. H. (Modern medical technology, 2019)
During the recent years the number of the wounded and killed due to firearms use both in Ukraine and in the majority of the world countries has increased. Therefore, examination of gunshot injuries is rather topical issue now in forensic medicine, and it is a considerable comprehensive question.Transience of incidences with the use of firearms in the majority of cases does not enable to find a real picture of circumstances when these incidences occur. Therefore, the issues of traumatic factor identification in these cases, especially with perforating and tangential injuries, are very important in forensic medicine, but remain elucidated insufficiently. At the same time, a dynamic development of upto-date computer technologies enables to increase the level of visualization, forensic diagnostics of injuries and substantiation of expert conclusions in case of gunshot injuries. Purpose of the study. To study diagnostic possibilities of three-dimensional spatial reconstruction method for forensic identification of the main traumatic factor in case of gunshot injuries. Materials and methods. Ballistic plasticine and gel, fragments of pig skin with subcutaneous fat, fragments of biological tissues with gunshot injuries were used as the material for the study. The obtained experimental gunshot injuries (45 cases) and cases of injuries from the expert practice (30 cases) were subjected to photogrammetric with possibility to obtain a three-dimensional spatial model of every injury by means of the computer program Agisoft Photoscan. Results. The studies conducted differ from the existing ones by their novelty, higher inventive and scientific-practical level. Three-dimensional spatial digital models of the injured biological tissues and their imitators will be designed, examined and analyzed for the first time, and the diagnostic criteria for forensic identification of the main traumatic factor of gunshot body injuries will be developed. The obtained textured models of gunshot injuries in «Obj» format can be imported into the program 3dsMax, which enables to examine linear sizes of every fragment of a wound canal with higher accuracy (to 0,001 cm) in comparison with classical methods of examination. The results obtained while conducting the study enable not only to develop computer threedimensional digital models of gunshot body injuries, but examine their character and morphologic peculiarities in forensic practice on an up-to-date scientific level. All the mentioned above enables to formulate and substantiate new, more accurate forensic diagnostic identification criteria of the main traumatic factor of gunshot body injuries. Conclusion. Introduction of up-to date computer technologies into the practice of forensic medicine will enable to determine identifying peculiarities of the main traumatic factor in case of gunshot injuries with a higher accuracy.